1998
DOI: 10.1093/bja/80.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Leucocyte distribution during sevoflurane anaesthesia

Abstract: We have examined if sevoflurane anaesthesia per se modified the number of circulating leucocytes in humans. Fifty-nine patients undergoing elective surgery were anaesthetized with sevoflurane in oxygen. The inhaled concentration was increased gradually to 5% and maintained for 20 min. Arterial blood samples were obtained before induction of anaesthesia and at 20 min. While the total number of leucocytes remained constant, circulating neutrophils decreased (mean 3370 (SD 1030) mm-3 to 3170 (940) mm-3; P < 0.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
1
17
2
4
Order By: Relevance
“…there are numerous in vitro studies investigating the effects of inhalant anesthetics on peripheral blood lymphocytes, and to a lesser extent on other cell types, while in vivo studies in animals and humans are very rare. According to MORISAKI et al (1998), total leukocyte count did not change following sevoflurane anesthesia, but the number of neutrophils decreased and the number of lymphocytes increased, which is in contrast to the results obtained in our study. Unlike the study cited above, the results reported by PUIG et al (2002) are consistent with our study.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…there are numerous in vitro studies investigating the effects of inhalant anesthetics on peripheral blood lymphocytes, and to a lesser extent on other cell types, while in vivo studies in animals and humans are very rare. According to MORISAKI et al (1998), total leukocyte count did not change following sevoflurane anesthesia, but the number of neutrophils decreased and the number of lymphocytes increased, which is in contrast to the results obtained in our study. Unlike the study cited above, the results reported by PUIG et al (2002) are consistent with our study.…”
contrasting
confidence: 99%
“…Isoflurane (TYTHER et al, 2001) and sevoflurane (TYTHER et al, 2003) were found to induce dose-dependent inhibition of polymorphonuclear neutrophil apoptosis in vivo and in vitro. as reported by MORISAKI et al (1998), total lymphocyte count did not change following sevoflurane anesthesia, but neutrophil count was observed to decrease while lymphocyte count increased. Data on repeated sevoflurane exposure are scarce and no major differences have been described between the adverse effects caused by initial and repeated sevoflurane exposure.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Inhalational anaesthetics induced different effects on lymphocytes. Some studies have showed an increase in lymphocyte counts after sevoflurane, halothane and desflurane anaesthesia 6,13,19 , while others showed lower counts 10,20 . Sevoflurane and isoflurane induced lymphocyte apoptosis 22 16,18 .…”
Section: Lymphocytesmentioning
confidence: 99%
“…Sevoflurane and isoflurane induced lymphocyte apoptosis 22 16,18 . Propofol and desflurane increase neutrophil counts in peripheral circulating blood 13,14 , although several studies have reported contradictory effects of sevoflurane on neutrophil count 13,14,19 .…”
Section: Lymphocytesmentioning
confidence: 99%